Blueprint for Screenwriting : a Writer's Guide to Creativity, Craft, and Career. - Ballon, Rachel Friedman (Lawrence Erlbaum Associates, 2004)
Demystifies the writing process by developing a "blueprint" for writers to follow for each new screenplay - from original concept to completed script. Author Rachel Ballon explores the writing craft and emphasizes creativity in the writing process.